Sexual Orientation, Ideology, and Philosophical Method - Andler Matthew (Journal of Social Ontology, 2020)
Here, I examine the epistemic relation between beliefs about the nature of sexual orientation (e.g. beliefs concerning whether orientation is dispositional) and beliefs about the taxonomy of orientation categories (e.g. beliefs concerning whether polyamorous is an orientation category). Current philosophical research gives epistemic priority to the former class of beliefs, such that beliefs about the taxonomy of orientation categories tend to be jettisoned or revised in cases of conflict with beliefs about the nature of sexual orientation. Yet, considering the influence of ideology on beliefs about socially significant phenomena, I argue for an epistemic reversal.